Work outside the employer’s premises - legal regime and organization challenges during and after the Covid-19 pandemic - Ristić, Andrijana (Glasnik Advokatske komore Vojvodine, 2023)
The outbreak of the Covid-19 epidemic led to an unexpected increase in the importance of working outside the employer’s premises, which was identified as one of the ways to continue doing business despite measures introduced to preserve public health. As work outside the employer’s premises didn’t have significant importance before the epidemic, due to the cautious attitude of employers and employees towards it, adequate attention was not paid to the regulation of this issue at the domestic and international level. This paper is aimed to answer the question of whether the attitudes of employees and employers towards this way of organizing work have changed after the onset of extraordinary health circumstances, as well as to determine whether the work outside the employer’s premises is adequately regulated in the Republic of Serbia. By answering these questions, we tried to determine which issues need to be regulated in a more adequate manner in the future. We answered these questions by conducting a survey with 40 employee – respondents, as well as by analysis of the results of the already conducted research and of legal and sub-legal texts that regulate this issue in our country. We concluded that the attitudes of employers and employees towards work outside of the employer’s premises have changed to being more positive and that based on this fact, it can be assumed that the importance of working outside the employer’s premises will be more significant in the future. We have also identified issues that require better regulation in the near future and indicated in which way we believe this should be done.